The Effect Of Welding Current And Electrodes On The Results Of AISI 1045 Steel Welding Strength By Impact Testing - Dede Zulrahman; Anis Siti Nurrohkayati (Universitas Muhammadiyah Sidoarjo, 2022)
Welding is an activity of joining two or more metals by heating them until they melt, in which the melted or melted workpieces will unite with the help of additional materials to form a connection or a whole piece of metal. The purpose of this study was to determine the effect of welding current, type of electrode and pattern of electrode movement on the strength of the welds against the impact test in order to produce optimal welding strength. The method used in this study is the Taguchi Method. This study used a SMAW welding machine with a 1G welding position. The material used in this research is AISI 1045 steel. The experimental design uses L4 (23) which has been designed by Orthoghonal Array. Next, the welding process and impact test are carried out. The results of the Impact Test were then analyzed using ANOVA. The results of this study are that the highest percentage yield value for the strength of the weld results is found in the type of electrode with a percentage of 21% and the lowest percentage value for the strength of the weld results is in the movement pattern of the electrode with a percentage of 10%.